Model of thermal field smart card authentication modules in the computerized system - Молодецька, Катерина Валеріївна (Ukrainian Information Security Research Journal, 2012)
An analytical model of the thermal field module smart-card authentication device, built using a method based on the algebraic properties of differential spectra is proposed. The comparison of the results of research with other known methods is perform. Proposed in the article the mathematical model of the thermal field of smart-cards can be used to create secure user authentication modules in computerized systems.